Case report: A 10-year prognosis of neonatal diabetes caused by a novel INS gene mutation - Tian, Mengting; Feng, Yi; Liu, Yanyan; Wang, Hua (Frontiers in Endocrinology, 2023)
Background: Neonatal diabetes mellitus (NDM) is a rare form of diabetes. We analyzed a novel insulin gene (INS) mutation of a Chinese permanent neonatal diabetes mellitus (PNDM) patient to explore the clinical and genetic characteristics and put forward some opinions on treatment and its long-term management. Case description: A proband was recruited who was diagnosed with permanent neonatal diabetes on his first day after birth. His clinical and follow-up data were collected for 10 years. All of the family members were given an oral glucose tolerance test. Whole exome sequencing was performed on the proband, and the genomic DNA of family members was used for verification by first-generation Sanger sequencing technology. The pathogenic variant was screened according to the American College of Medical Genetics and Genomics classification guidelines and the clinical phenotype of the patient. Diagnostic assessment: The proband was diagnosed on the first day after birth, presenting with low birth weight, progressive hyperglycemia, and insulin deficiency. His parents and grandfathers were confirmed to have normal blood sugar levels. A novel homozygous mutation of c.1T>C in the INS gene was detected in the proband, located in the initiation codon. The heterozygous mutations were found in four family members, including his mother, father, and grandfathers. With regular insulin injections, long-term regular follow-up, close monitoring of blood glucose, balanced exercise and diet, and psychological and mutual family support, the blood glucose level was well controlled; there were no acute or chronic complications during this decade. The patient’s growth and nervous system development are now no different to those of the same age. Conclusion: A favorable prognosis is presented for a permanent neonatal diabetes mellitus (PNDM) patient with a novel mutation in the INS gene in China. The present findings indicate that the genetic diagnosis, early use of insulin, close monitoring of blood glucose, and psychological and mutual family support for patients with INS mutation are necessary for their favorable long-term prognosis.